The mediating role of Tawakkul and perceived social competence between locus of control and flourishing - Gondal, Muhammad Usama (Mental health, religion & culture, 2024)
The chief objective of the study was to investigate the mediating role of Tawakkul with perceived social competence between locus of control and flourishing in a purposive sample of 300 Muslim adults. Urdu versions of Tawakkul Scale, Diener Flourishing Scale, Perceived Social Competence Scale II and Multidimensional Locus of Control Scale were used to measure the focal variables. Tawakkul had moderate to strong positive relations with perceived social competence, flourishing and internal locus of control and a weak positive relationship with an external locus of control. Path analysis revealed that Tawakkul mediated the relationships between perceived social competence, flourishing and locus of control. Additionally, perceived social competence mediated the relationships between locus of control, Tawakkul and flourishing. Serial mediation indicated that locus of control and flourishing were mediated by perceived social competence and Tawakkul. The study’s implications and future research recommendations are discussed.